The Impact of Meniscal Treatment on Functional Outcomes Six Months After Anterior Cruciate Ligament Reconstruction (107). Issue 10 (31st October 2021) - Casp, Aaron; Bodkin, Stephan; Gwathmey, F. Winston; Werner, Brian; Miller, Mark; Diduch, David; Brockmeier, Stephen; Hart, Joseph
Objectives: The incidence of anterior cruciate ligament (ACL) injuries continues to rise, and meniscal injuries are commonly associated with these tears. Treatment of meniscal injuries can impart delayed weightbearing range-of-motion restrictions, which can affect the post-operative rehabilitation protocol. These limitations after a meniscal repair could change how patients are managed and progressed through rehab. The effect of the meniscal treatment and subsequent restrictions on strength recovery after ACL reconstruction (ACLR) is unclear and may affect return-to-play assessments. The purpose of this study was to compare strength, jumping performance and patient reported outcomes between isolated ACLR patients and those undergoing surgical intervention for meniscal pathology at the time of ACLR surgery at a scheduled functional testing assessment an average of 6 months after surgery. Our hypothesis is that those undergoing meniscal repair will have lower strength recovery due to post-operative restrictions. Methods: In this retrospective cohort study, ACLR patients and healthy controls completed patient-reported outcomes (IKDC and KOOS), underwent bilateral isokinetic and isometric strength tests of the knee extensor and flexor groups, as well as functional hop testing as part of a return-to-sport test battery at 5-7 months post-operatively. ACLR patients were stratified as isolated ACLR, ACLR+Meniscectomy (ACLR-MS), ACLR+Meniscal Repair (ACLR-MR) and compared to healthy controls. Patients treated with meniscus repair were restricted to partial weight bearing and to 90 degrees of knee flexion for the first 6 weeks post-surgery. Comparisons were performed between meniscal treatment groups with regard to demographics, patient reported outcomes scales, knee extensor and flexor strength, while stratifying by graft type. Results: 305 participants, including 165 ACLR patients (50 isolated ACLR, 71 ACLR + Meniscal Repair, 44 ACLR + Meniscectomy) and 140 healthy controls were included with an average time post-operatively to functional testing of 5.96±0.47 months. Heathy controls demonstrated higher subjective knee function, unilateral peak extensor torque, and limb symmetry than all meniscal subgroups (p<.001). There were no differences between the IKDC, KOOS subscales, or in unilateral or limb symmetry measures of peak knee extensor or flexor torque between ACLR, ACLR+MS, and ACLR+MR patients (all p-values>.05). Conclusions: Persistent weakness, asymmetry and reduced subjective outcome scores measured at approximately 6 months post index surgery were not influenced by meniscus treatment. Knee flexor and extensor strength, limb symmetry, and patient reported outcomes did not significantly differ across patients undergoing isolated ACLR, ACL + Meniscus Repair, and ACL + meniscectomy. These findings suggest that the weightbearing and range-of-motion restrictions associated with meniscus repair recovery do not result in loss of early strength or patient reported outcomes, and they can be progressed through therapy accordingly.